The role of talent management in enhancing creative performance at the Ministry of Foreign Affairs in Jeddah for year 2022 - Alshehri, Fatmah Ali (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to know the reality of talent management in the Ministry of Foreign Affairs in Jeddah and the extent of this in enhancing the creative performance of employees, and to know the impact of demographic variables (gender, academic qualification, years of experience) on them, and talent management was measured according to its dimensions (attract, retain, develop, planning Job succession) on the creative performance dimensions (originality, fluency, flexibility, problem-solving). The researcher adopted the descriptive and analytical approach and used the questionnaire as a tool to suit the nature of the study. It was distributed to workers in a simple random way, and the number of response was (70) out of (100) employees. And a female employee, and SPSS statistical analysis software was used to analyze the evidence and arrive at the results. As a result, the most important results were reached, which is the existence of a statistically significant positive correlation relationship between talent management and creative performance in the Ministry of Foreign Affairs in Jeddah, where the Pearson correlation coefficient reached (0.674), which is a statistically significant value at the level of significance (0.001), and the presence of significant differences A statistic between the averages of the sample’s scores on the creative performance scale according to academic qualification, while there are no statistically significant differences between the average scores of the sample individuals on the creative performance scale according to gender and years of experience. The researcher recommended attracting distinguished talents and skills through secondment or the use of external institutions in order to introduce human energies that work on renewal and development in work, and to provide all kinds of incentives, whether material or moral, to talented and creative people by the higher management fairly in appreciation of their efforts, which in turn will contribute to preserving and motivating them in creative performance, as well as working on preparing a succession plan for leadership positions and working on it by the higher management in order to develop and maintain distinguished talents and participate in the nomination of the selection of their superiors.